Bigger Participation and Wider Collaboration: Second Vatican Council as an Arena of Creation and its Indonesian Contextualization - Martinus Joko Lelono (International Journal of Indonesian Philosophy & Theology, 2025)
The Second Vatican Council is an opportunity for the Catholic church in fostering a new perspective on looking at her presence both among the Catholic adherents and society in general. The Post-conciliar Catholic Church lives with particular social approach with two invitations at the same time: the invitation for the participation of a bigger number of Catholics in pastoral works belongs of the Church; and the encouragement for collaboration either among the Catholics or with those from other Churches or different religions. Along with the exploration toward documents that related to interreligious dialogue, this study contributes in looking at the new ecclesiology. The Post-conciliar Catholic Church is no longer a community that looking at herself as the one above society, but rather as the one among the others. In the light of Pierre Bourdieu’s theory of field, capital and habitus, this study concludes this new ecclesiology, both in the global and Indonesian local context, is accompanying the Church to be a community that fostering internal participation and elaborating external collaboration.